Victims, Crime and Society - Davies, Pamela (2007)
Organized around the intersecting social divisions of class, race, age and gender, the book provides an engaging and authoritative overview of the nature of victimisation in society. In addition to a review of the major theoretical developments in relation to understanding aspects of victimization in society, individual chapters explore the political and social context of victimisation and the historical, comparative and contemporary research and scholarly work on it